1999
DOI: 10.1053/seiz.1999.0286
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment of well-being in a group of children with epilepsy

Abstract: Epilepsy is common in childhood, the prevalence being about five per 1000 children. The purpose of this study was to assess well-being in children with controlled epilepsy (but did not include those with obvious neurodeficits such as mental retardation or cerebral palsy) and compare them with age-matched healthy children. The patient group comprised of 31 children, 12 boys and 19 girls, whereas the control population group consisted of 342 children, 176 boys and 166 girls who were all in good health. All child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…The fact they had to take medications or attend clinic appointment regularly did not affect their satisfaction towards their own health. This result is similar to previous findings in adolescents with controlled epilepsy [31]. One possible explanation is that people with disabilities do not consider their disability a health problem, even if associated with medications or adaptive equipment use.…”
Section: Discussionsupporting
confidence: 90%
“…The fact they had to take medications or attend clinic appointment regularly did not affect their satisfaction towards their own health. This result is similar to previous findings in adolescents with controlled epilepsy [31]. One possible explanation is that people with disabilities do not consider their disability a health problem, even if associated with medications or adaptive equipment use.…”
Section: Discussionsupporting
confidence: 90%
“…Severity of epilepsy may account for differences in findings concerning self-esteem. Present findings are supported by a recent study (29) that found no differences between children with well controlled epilepsy and age-matched healthy children on a self-report measure of well-being (i.e., self-esteem, alertness, mood, elation, stability, and vitality).…”
Section: Discussionsupporting
confidence: 89%
“…Face-validity was noted when the level of concern increased as worsening of seizure control occurred. Interestingly, Norrby et al (24) found that children with controlled epilepsy and no obvious neurodeficits did not differ from aged-matched controls when describing themselves using 39 bipolar adjectives and a VAS of well-being. Austin et al (25), Hoare and Kerley (26), and Carpay et al (27) addressed selected concerns of children with epilepsy, such as relationships with siblings, stigma, self-esteem, and restrictions.…”
Section: Discussionmentioning
confidence: 99%